Whole-exome rare-variant analysis of Alzheimer's disease and related biomarker traits - Küçükali, Fahri; Neumann, Alexander; Van Dongen, Jasper; De Pooter, Tim; Joris, Geert; De Rijk, Peter; Ohlei, Olena; Dobricic, Valerija; Bos, Isabelle; Vos, Stephanie J. B.; Engelborghs, Sebastiaan; De Roeck, Ellen; et al. (Alzheimer's and dementia, 2023)
Abstract Introduction Despite increasing evidence of a role of rare genetic variation in the risk of Alzheimer's disease (AD), limited attention has been paid to its contribution to AD-related biomarker traits indicative of AD-relevant pathophysiological processes. Methods We performed whole-exome gene-based rare-variant association studies (RVASs) of 17 AD-related traits on whole-exome sequencing (WES) data generated in the European Medical Information Framework for Alzheimer's Disease Multimodal Biomarker Discovery (EMIF-AD MBD) study (n = 450) and whole-genome sequencing (WGS) data from ADNI (n = 808). Results Mutation screening revealed a novel probably pathogenic mutation (PSEN1 p.Leu232Phe). Gene-based RVAS revealed the exome-wide significant contribution of rare coding variation in RBKS and OR7A10 to cognitive performance and protection against left hippocampal atrophy, respectively. Discussion The identification of these novel gene?trait associations offers new perspectives into the role of rare coding variation in the distinct pathophysiological processes culminating in AD, which may lead to identification of novel therapeutic and diagnostic targets.
Erstmals veröffentlicht: 04. Dezember 2022
Gesehen am 04.06.2024